Controlled droplet transport to target on a high adhesion surface with multi-gradients - Deng, Siyan (Sci Rep, 2017)
We introduce multi-gradients including Laplace pressure gradient, wettable gradient and wettable different gradient on a high adhesion surface via special wedge-pattern and improved anodic oxidation method. As a result of the cooperative effect mentioned above, controlled directional motion of a droplet on a high adhesion surface is realized, even when the surface is turned upside down. The droplet motion can be predicted and the movement distances can be controlled by simply adjusting the wedge angle and droplet volume. More interestingly, when Laplace pressure gradient is introduced on a V-shaped wettable gradient surface, two droplets can move toward one another as designed.